2014
DOI: 10.1039/c4ob00638k
|View full text |Cite
|
Sign up to set email alerts
|

CuI catalyzed sulfonylation of organozinc reagents with sulfonyl halides

Abstract: In this study, a facile CuI catalyzed synthesis of sulfones involving a nucleophilic addition of functionalized organozinc reagents to organic sulfonyl chlorides is realized. This reaction proceeds efficiently at room temperature, giving rise to various functional group substituted sulfones, generally in moderate to high yields. The method provides a novel, simple, and promising strategy for functionalized sulfone synthesis in the research field of sulfur chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 56 publications
2
11
0
1
Order By: Relevance
“…It is known that aldehydes can form hemiacetal intermediates when they are treated with metallic alkoxide such as in Tishchenko reaction or Cannizzaro reaction . Previously, during our research on the reaction of organozinc reagents with sulfonyl chlorides, we observed that when sulfonyl chloride was treated with phenylzinc phenoxide (PhZnOPh), the phenoxide anion transferred preferentially over the phenyl anion to the sulfonyl group. Data from Table clearly show that the employment of a less bulky zinc alkoxide favors the ketone product which is exactly contrary to the common recognition that a bulky metal alkoxide favors the Oppenauer oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that aldehydes can form hemiacetal intermediates when they are treated with metallic alkoxide such as in Tishchenko reaction or Cannizzaro reaction . Previously, during our research on the reaction of organozinc reagents with sulfonyl chlorides, we observed that when sulfonyl chloride was treated with phenylzinc phenoxide (PhZnOPh), the phenoxide anion transferred preferentially over the phenyl anion to the sulfonyl group. Data from Table clearly show that the employment of a less bulky zinc alkoxide favors the ketone product which is exactly contrary to the common recognition that a bulky metal alkoxide favors the Oppenauer oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ) δ = 2.45 (s, 3 H), 4.34 (s, 2 H), 7.21−7.26 (m, 2 H), 7.27−7.31 (m, 2 H), 7.49−7.55 (m, 2 H), 7.56−7.61 (m, 2 H) ppm; 13 C{1H}NMR (100 MHz, CDCl 3 ) δ = 21.7, 62.5, 112.8, 118.2, 128.5, 129.8, 131.5, 132.2, 133.6, 134.6, 145.32 The obtained data match those reported in the literature. 33 1-Nitro-4-(tosylmethyl)benzene (6ak) [CAS: 61081-32-1]. The title compound was prepared according to method B from p-tolyl methyl sulfone (85.1 mg, 0.50 mmol), 4-bromo-1-nitrobenzene (121 mg, 0.60 mmol), Pd(dba) 2 (28.8 mg, 0.05 mmol), XPhos (25.1 mg, 0.05 mmol), and tmp·ZnCl·LiCl solution (2.5 M, 1.25 mmol, 5.0 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…Previously, we developed a CuI catalyzed synthesis of arylsulfones from organozinc reagents and arylsulfonyl chlorides. 17 During this study, we accidentally found that when PPh 3 was employed as the ligand, thioether can be formed unexpectedly. Owing to our interests on the synthesis and application of organozinc reagents in organic synthesis, 18 we here report an CuI promoted sulfenylation of organozinc reagents employing commercially available arylsulfonyl chlorides as the sulfur source under mild reaction (Scheme 1).…”
mentioning
confidence: 96%